Βeta-adrenergic receptor reactivity of erythrocyte membranes in patients with left or right atrial dilatation against the background of atrial fibrillation - E. F. Muslimova; V. O. Popova; T. Y. Rebrova; E. A. Archakov; R. E. Batalov; S. A. Afanasiev (Бюллетень сибирской медицины)
Hyperactivation of the sympathoadrenal system (SAS) leads to desensitization of β1-adrenergic receptors (β1-AR). This contributes to aggravation of myocardial contractile dysfunction and development of arrhythmias, including atrial fibrillation (AF). An indirect indicator of the viability of β1-AR is β-adrenergic receptor reactivity of erythrocyte membranes (β-ARM).Aim. To evaluate β-ARM in patients with different forms of AF, including left (LAD) or right (RAD) atrial dilation.Materials and methods. The sample included 38 patients, 65.8% of whom had paroxysmal AF, 21% had persistent AF, and 13.2% had long-standing persistent AF. All patients received surgical treatment for AF by radiofrequency ablation or cryoablation. LAD was detected in 39.4% of patients, RAD – in 34.2% of patients. Βeta-ARM was determined before treatment, as well as at 3 days and at 12 months after ablation.Results. The groups of patients with different forms of AF, as well as patients with LAD / RAD and without it showed comparable values of β-ARM at different measurement periods. In the group of patients without LAD / RAD, β-ARM increased 3 days after ablation compared to β-ARM before the treatment (p = 0.002 / p = 0.004) and returned to the pre-treatment level after 3 months. At the same time, in the group of patients with LAD / RAD, β-ARM did not significantly change before the ablation and in different periods after it.Conclusion. In patients with AF without LAD / RAD, we detected an increase in β-ARM 3 days after the ablation compared to the level before the treatment and a decrease in the intensity of SAS 3 months after the surgery. In the presence of LAD / RAD, no changes in the β-ARM were revealed.